The Effects of Organic Wastes on Soil and Cotton Quality with respect to the Risk of Boron and Heavy Metal Pollution - Müzeyyen Seçer; Ömer Lütfü Elmaci; Şafak Ceylan (International Journal of Agronomy)
The effects on soil and cotton quality of organic wastes from medicinal and aromatic plant factories were investigated with regard to the risks of boron and heavy metal pollution. Oily cumin, oregano, oilless oregano wastes, and mineral fertilizers were applied to cotton in two field experiments performed in the years 2003 and 2006. The Pb content of the soil differed significantly in the 2003 experiment and oregano wastes had significantly decreasing effect. Boron of soil to which oily cumin wastes had been applied reached a toxic limit value in 2006. Boron in soil adversely affected long fibres; B in leaves had a positive effect on the fineness of fibres in 2006. Soil Ni adversely affected plant height in 2006 and seed cotton yield in 2003. Leaf Ni had an adverse effect on fibre elasticity in 2006. Soil Co increased ginning out-turn and Cr decreased the fibre fineness of cotton in 2003.